Highway capacity manual : a guide for multimodal mobility analysis. (Transportation Research Board, 2016)
"This new edition of the HCM adds a subtitle: A Guide for Multimodal Mobility Analysis. This underscores the HCM's focus on evaluating the operational performance of several modes, including pedestrians and bicycles, and their interactions. It is called the 6th Edition, with no year attached, and each chapter indicates a version number, to allow for updates."--Page V1-1